A randomised controlled trial of azithromycin following surgery for trachomatous trichiasis in the Gambia. Issue 10 (16th September 2005) - Burton, M J; Kinteh, F; Jallow, O; Sillah, A; Bah, M; Faye, M; Aryee, E A N; Ikumapayi, U N; Alexander, N D E; Adegbola, R A; Faal, H; Mabey, D C W; et al.
Abstract : Background/aim: Trachomatous trichiasis frequently returns following surgery. Several factors may promote recurrence: preoperative disease severity, surgeon ability, surgical procedure, healing responses, and infection. This study investigates whether enhanced control of infection, both of Chlamydia trachomatis and other bacteria, with azithromycin can improve surgical outcome in a trachoma control programme. Methods: Individuals with trachomatous trichiasis were examined and operated. After surgery patients were randomised to the azithromycin or control group. The azithromycin group and children in their household were given a dose of azithromycin. Antibiotic treatment was repeated at 6 months. All patients were reassessed at 6 months and 12 months. Samples were collected for C trachomatis polymerase chain reaction and general microbiology at each examination. Results: 451 patients were enrolled. 426 (94%) were reassessed at 1 year, of whom 176 (41.3%) had one or more lashes touching the eye and 84 (19.7%) had five or more lashes. There was no difference in trichiasis recurrence between the azithromycin and control group. Recurrent trichiasis was significantly associated with more severe preoperative trichiasis, bacterial infection, and severe conjunctival inflammation at 12 months. Significant variability in outcome was found between surgeons. Visual acuity and symptoms significantly improved following surgery. Conclusion: In this setting, with a low prevalence of active trachoma, azithromycin did not improve the outcome of trichiasis surgery conducted by a trachoma control programme. Audit of trichiasis surgery should be routine.